The Impact of Multiple Long-Term Care Services Use on Dementia and Nondementia Caregivers' Health Care Utilization and Costs. (November 2022) - Chan, Su-Yuan; Yu, Hsiao-Wei; Yang, Ming-Ching; Lee, Yue-Chune; Chen, Ya-Mei
Background: The study examined the effects of multiple long-term care (LTC) services (i.e., using both social and professional care services) on caregivers of service recipients with and without dementia. Methods: We retrieved data for 10, 771 caregivers of older adults in the Ten-Year Long-Term Care Project (TLTCP) in Taiwan. We examined the effects of care recipients' initial prescription of single or multiple LTC services on their caregivers' healthcare services use, including outpatient, emergency department (ED), and inpatient services. Results: For care recipients prescribed a single LTC service, dementia caregivers had 0.82 more ED visits and 10.4% higher total fees than nondementia caregivers ( p < .05). However, for care recipients prescribed multiple LTC services, dementia caregivers and nondementia caregivers used healthcare services at similar levels, and dementia caregivers had 3.5% lower per-visit outpatient fees ( p < .05). Discussion: Providing multiple LTC services for people with dementia results in great benefit to their caregivers.